Measure and Capacity of Wandering Domains in Gevrey Near-integrable Exact Symplectic Systems - Lazzarini, Laurent; Marco, Jean-Pierre; Sauzin, David (Memoirs of the American Mathematical Society, 2019)
A wandering domain for a diffeomorphism We first prove that the measure (or the capacity) of these wandering domains is exponentially small, with an upper bound of the form The second part of the paper is devoted to the construction of near-integrable Gevrey systems possessing wandering domains, for which the capacity (and thus the measure) can be estimated from below. We suppose